Consumption of ultra-processed foods by foreign-born adults rise with increased levels of acculturation in the United States - Barb, Jennifer J.; Yang, Li; Martinez-Steele, Euridice; Ahmed, Ayaan; Medina, Patricia V.; Valencia, E. Michael; Roberts, Anna E.; Farmer, Nicole; Wallen, Gwenyth R. (Frontiers in Public Health, 2025)
ObjectiveUltra-processed food (UPF) consumption has been linked to increased risks of negative health outcomes such as type 2 diabetes, obesity, and all-cause mortality. Some studies have shown an increase of UPF consumption with acculturation, whereas the influence of the Western diet on non-US born individuals is an area of increasing interest. The aim of this work was to investigate UPF consumption with an acculturation index and to assess whether there was an interaction of UPF consumption with race/ethnicity in non-US born adults.MethodsDietary intake of non-US born adults participating in the National Health and Nutrition Examination Survey (NHANES) between 2011 and 2018 was assessed using day one of 24-h dietary recall, and the relative daily energy intake comprised of UPFs was used as the outcome of interest. The effect of acculturation assessed by an acculturation index (AcI) on UPF consumption was investigated after controlling for significant covariates. Complex survey sample regression analyses were used to evaluate the association between UPF consumption and AcI.ResultsPopulation sample (n = 3,639) was comprised of non-US born adults (50% male) between 19 and 70 (43.1 ± 0.40) years of age. Of the adults assessed, 42.2% had lower AcI scores of 0 to 2, whereas 57.8% were more accultured (AcI scores of 3–5). Overall, dietary energy from UPFs was about 43.3%. When controlling for co-variates, acculturation was significantly associated with UPF consumption (β = 0.03, s.e. = 0.004, p < 0.001), meaning that for every unit increase in AcI score, there was a 3 % increase in mean UPF consumption. When the interaction between AcI and race/ethnicity was assessed, there was no difference in the impact of AcI on UPF consumption among race/ethnicity groups (p = 0.052).ConclusionOur findings indicate that greater acculturation is associated with higher UPF consumption. Given the links between high UPF consumption and adverse health outcomes, targeted interventions that promote healthier dietary choices—while preserving culturally relevant eating habits—are essential to support the well-being of non-US born populations.